A potential full Heusler thermoelectric material CO2ZrZ (Z=Al, Si, Ga and Sn) in low temperature: An Ab-initio investigation. (October 2021) - Remil, G.; Zitouni, A.; Bouadjemi, B.; Houari, M.; Abbad, A.; Benstaali, W.; Cherid, S.; Matougui, M.; Lantri, T.; Bentata, S.
Abstract: The structural, electronic, magnetic, elastic and thermoelectric properties of full-Heusler alloys Co2 ZrZ (Z = Al, Si, Ga and Sn) are investigated using the augmented plane wave method (FP-LAPW) based on the framework of spin density functional theory. The term of the exchange and correlation potential (XC), is treated by the generalized gradient approximation GGA and Trans-Blaha-modified Becke–Johnson (TB-mBJ). The results obtained showed that the Cu2 MnAl-type structure has more stable energy than the Hg2 CuTi-type structure for all the full-Heusler studied. From electronic calculations, it is found that all the compounds studied have an indirect band gap with a half-metallic behavior. Furthermore, we also found that all materials have integral magnetic moments which are mainly due to 100% spin polarization at Fermi energy. The calculated elastic constants and the anisotropy shear factors indicate that these compounds have a ductile character and are mechanically stable. Finally, we calculated the thermoelectric properties by applying Boltzmann theory as implemented in the BoltzTraP code. The results obtained for the merit factor ( ZT ) and Seebeck coefficient ( S ) make these materials promising candidates in thermoelectric applications and in spintronics devices. Highlights: Investigation of optoelectronic and thermoelectric properties for CO2 ZrZ (Z = Al, Si, Ga and Sn) using Wien2k code. Heusler alloys with indirect band gap and a half-metallic behavior. The studied compounds have a ductile character and stable mechanically. High electrical conductivity and a figure of merit which is close to unity at low temperatures. They can be considered as a source of low-temperature energy to produce electricity.